TINJAUAN YURIDIS TENTANG PATEN BERDASARKAN UNDANG-UNDANG PATEN NOMOR 14 TAHUN 2001 - Hanafi, Mashunah (Syariah: Jurnal Hukum dan Pemikiran, 2013)
Paten is an intellectual work which is protected by the State through the law or intellectual property rights, given to the inventors for improving their inventions during the period of time. Inventor is a person or a group of people who has the same idea to run the invention as a solution for specific problem in the field of technology that could significantly improve or simply adjust their products and processes.